Initial Study of Learning Cycle 5E Based Learning Media Development to Improve Collaboration Skills In Elementary School - Hendra, Putra You; Yulianti, Dwi; Adha, Muhammad Mona; Firdaus, Rangga (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
This research is an initial study that aims to describe the condition of collaborative learning in elementary schools as a basis for developing learning media based on the Learning Cycle 5E model. The background of the research is based on the low collaboration skills of students and the unoptimal utilization of digital media and interactive approaches by teachers. The research method used descriptive quantitative and qualitative approaches with data collection techniques in the form of questionnaires (76 elementary school teachers), in-depth interviews (4 classroom teachers), and observations of 24 fourth grade students in Selagai Lingga District. The results show that 86% of teachers have not used technology-based media, 80% have not implemented interactive learning models, and 92% assess students' collaboration skills as low. The observation mean of 2.35 confirmed the weakness of five collaboration indicators: cooperation, flexibility, responsibility, compromise and communication. The Learning Cycle 5E model is considered relevant to increase students' active involvement, and the development of technology-based media such as Articulate Storyline III has the potential to strengthen collaborative activities in learning. Thus, the development of LC5E-based learning media is a strategic solution to improve students' collaboration skills contextually and applicatively.